ANALISIS PENGARUH DESAIN KERJA DAN SISTEM PEMBERIAN PENGHARGAAN TERHADAP KEPUASAN KERJA KARYAWAN PT. SUMINSURYA MESINDOLESTARI MEDAN - Alfonsius Alfonsius; Syawaluddin Syawaluddin (STIE-PMCI, 2018)
In the era of competitive business nowadays, many challenges are faced by companies, especially for those engaged in steel industry. To face those challenges, the company should have high productive and committed human resource who can work for long period. As a consequence, employee job satisfaction is the most important factor to be considered by the company to retain those good employees. The purpose of this study is to find out the influence between job design and rewarding system on employee job satisfaction. Job design and rewarding system is related each other as the significant role in increasing employee job satisfaction. A well-organized job design will create a clear purpose for them, so that they will be motivated because they know the significance of what they are working for. In the other hand, employees will do their best when what they hope from their hard work are rewarded appropriately by the company.The method used in this study is a survey approach, the type of research is quantitative descriptive, and the characteristic of research is explanatory research. The population of this research is all employee of PT. Suminsurya Mesindolestari Medan with a population of 60 people and the samples are 30 people from PT. Growth Sumatra Industry. The methods of collecting data are distribution of questionnaires, interviews, observation, and documentary studies. The variables are examined with a Likert scale. The model analysis of the data used to answer the first hypothesis is a multiple regression and simple regression for the second hypothesis.Research result that the job design and reward system jointly and significantly affect on the employee job satisfaction at PT. Suminsurya Mesindolestari, and partially the most dominant factor is reward system.Keywords: Job Design, Reward System, Employee Job Satisfaction, EmployeeÂ